UPAYA KOMUNIKASI INTERPERSONAL ANTARA KEPALA SEKOLAH DAN GURU DI SMP IT FAJAR ILAHI 2 SUNGAI BEDUK BATAM - Husneidy Syah Zikra; ALI MASHAR; ITA EVINA (UNISAN JURNAL, 2024)
From the aftereffects of the review it is realized that the example of relational correspondence at SMP Negeri 6 Bandar Lampung Bandar Lampung City which incorporates: (1) The example of relational correspondence between the Principal and the instructor verbally at SMP Negeri 6 Bandar Lampung Bandar Lampung City The central verbal correspondence design is done up close and personal. eye to eye with the educator goes one way through good tidings, direct course both in gatherings and in the everyday workplace with an end goal to further develop instructor execution. (2) The correspondence example of the chief recorded as a hard copy is helped out through composed means, for example, an authority letter which is utilized to educate educators when there are standard gathering exercises. Catchphrases: Relational Communication, Principal, Oral correspondence Pattern, Written Communication Pattern